Overview of the Characteristics of Geriatric Patients with Skin Diseases at the Outpatient Polyclinic of RSP Ibnu Sina Makassar in 2022-2024 - Nurul Fadilah; Lisa Yuniati; Hanna Aulia Namirah; Sri Vitayani; Arina Fathiyyah Arifin (Universitas Muhammadiyah Malang, 2025)
The skin is the largest organ and plays an important role as a protector of the body. In geriatric populations, physiological changes in the skin due to aging increase susceptibility to various skin diseases. Local data on the characteristics of geriatric patients with skin diseases are still limited, especially in Makassar. This study aims to provide an overview of the characteristics of geriatric patients with skin diseases at Ibnu Sina Makassar Hospital. The research design was a cross-sectional descriptive study with a total sampling of 54 geriatric patients (≥60 years) who were treated at the Skin and Venerean Outpatient Polyclinic of RSP Ibnu Sina Makassar for the 2022–2024 period. Data was obtained through medical records, then analyzed descriptively using SPSS and Excel. Most patients were aged 60–74 years (74.1%), male (51.9%), and civil servant/retired (57.4%). As many as 74.1% of patients did not have comorbidities; Diabetes mellitus was the most comorbid (13%). Non-infectious skin diseases dominated (50%), followed by fungal infections (25.9%), bacterial (16.7%), and viral (7.4%). The most common diagnoses were senilic pruritus (20.4%), followed by tinea corporis (13%), as well as seborrheic dermatitis, lichen simplex, and shingles at 7.4% each. Geriatric patients with skin diseases at the Ibnu Sina Makassar Hospital Outpatient Polyclinic for the 2022–2024 period are dominated by 60–74 years old, male, and most of the jobs are civil servants/retirees. Non-infectious skin diseases, especially pruritus senilis, are the most common diagnoses. Education about elderly skin care and preventive approaches are needed to improve the quality of life of geriatric patients.